PELESTARIAN NASKAH KUNO DI MUSEUM NEGERI PROVINSI SUMATERA UTARA - Miftahul Jannah; Sori Monang; Muslih Faturrahman (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was conducted at the Museum Negeri Sumatera Utara, focusing on the critical issue of preserving ancient manuscripts, which hold significant influence on cultural heritage. The research problem is framed around two key questions: First, how does the Museum Negeri Sumatera Utara implement technical services for the preservation of its ancient manuscripts? Second, what are the challenges faced by the museum in carrying out the preservation of these valuable manuscripts?The purpose of this research is to elucidate the technical services employed in the preservation of ancient manuscripts at the Museum Negeri Sumatera Utara and to identify the various challenges encountered by the museum in this preservation process.The methodology adopted in this study is qualitative research. As explained by Sugiyono, qualitative research is a method used to investigate objects in their natural state, as opposed to the controlled environment of experimental research. The findings of this study underscore the importance of preserving ancient manuscripts, as the information they contain can provide valuable knowledge for future generations.